Keterampilan Profesional Konselor Karier: Kompetensi Esensial untuk Bimbingan yang Efektif - Afriyati, Vira; Pasmawati, Hermi (Yayasan Lembaga Studi Makwa, 2024)
This article discusses the essential professional skills in career counseling to assist individuals in understanding their potential, exploring career options, and making informed decisions based on their interests, values, and competencies. This study aims to identify and analyze the key competencies that career counselors must possess to provide effective services. The method used is a literature review by examining relevant theories and research. The discussion covers various critical aspects, such as the career counseling process, techniques used in counseling sessions, career assessment, and managing career information and technology. The analysis results indicate that career counselors must have strong communication skills, an in-depth understanding of career theories, the ability to interpret assessments, and proficiency in utilizing technology to support career guidance services. Additionally, continuous professional development is a crucial factor in enhancing service effectiveness and ensuring that career counselors can adapt to changes in the job market and the evolving needs of clients. This study contributes to the field of career counseling by providing a comprehensive synthesis of essential competencies required for career counselors, highlighting gaps in existing training and practice, and offering recommendations for future research and professional development programs. These findings are expected to serve as a reference for practitioners and researchers in designing more innovative, evidence-based, and responsive approaches to career challenges in the modern era. Thus, career counselors can provide more adaptive, relevant, and client-centered services.